2022
DOI: 10.1002/clc.23935
|View full text |Cite
|
Sign up to set email alerts
|

Nonadherence to lipid‐lowering therapy and strategies to improve adherence in patients with atherosclerotic cardiovascular disease

Abstract: Despite the availability of effective therapies that lower low‐density lipoprotein cholesterol (LDL‐C) levels in patients with atherosclerotic cardiovascular disease, many eligible patients are inadequately treated and their LDL‐C levels remain suboptimal. Patient nonadherence to lipid‐lowering therapy (LLT) is a major contributor to the failure of LDL‐C goal attainment. Several factors have been identified as contributing to LLT nonadherence, including healthcare disparities due to socioeconomic status, age, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 45 publications
0
19
0
3
Order By: Relevance
“…However, there exists a significant gap between what guidelines recommend for lipid-lowering therapy in ASCVD patients and what occurs in real-world practice [7,8]. In part, this is related to under-prescribing of statin intensity, which is most often due to statin intolerance, clinical inertia, insufficient monitoring of LDL-C levels and the difficulty of prescribing and high cost of some nongeneric lipid-lowering therapies such as the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors [9 ▪ ].…”
Section: Provider Levelmentioning
confidence: 99%
“…However, there exists a significant gap between what guidelines recommend for lipid-lowering therapy in ASCVD patients and what occurs in real-world practice [7,8]. In part, this is related to under-prescribing of statin intensity, which is most often due to statin intolerance, clinical inertia, insufficient monitoring of LDL-C levels and the difficulty of prescribing and high cost of some nongeneric lipid-lowering therapies such as the proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors [9 ▪ ].…”
Section: Provider Levelmentioning
confidence: 99%
“…Statins are a core treatment for FH and ASCVD, and poor adherence to statin therapy or discontinuation may diminish treatment benefit for the prevention of ASCVD in FH. Numerous studies have reported high rates of nonadherence to statin therapy in the real-world setting [5,26]. The magnitude and impact of poor adherence is higher in developing countries, given the disparities in health resources and inequalities in access to healthcare [5].…”
Section: Adherence To Lipid-lowering Treatmentmentioning
confidence: 99%
“…HCPs also need to be specifically trained in adherence management (such as behavioural counselling); shared strategies involving pharmacists and nurses in general practice can promote adherence to treatment [2 ▪▪ ]. HCPs should manage FH patients by following guideline-directed treatment recommendations [5]. A definite genetic diagnosis for FH may also motivate HCPs following guideline-recommended treatments [53].…”
Section: Enablers and Solutions To Improve Adherence To Treatment In ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Also important in future work will be to establish how generalisable are the findings, given the patients were drawn from a specific programme using an invasive management strategy and the New Zealand health care system where medication cost subsidies likely differ from those found elsewhere. Lastly, this novel and interesting work highlights the importance of education initiatives, shared decision making between patients and health professionals, and involvement of pharmacy-based programs pre- and post-discharge [ 8 ]; and, emphasises the importance of ongoing evaluation of adherence with patients and the need for further investigation into this important area.…”
mentioning
confidence: 99%